Hyperventilation syndrome and health-related quality of life: a study of undergraduate students - Daud, Azlina; Adnan, Aida Azilah; Esleem, Fadi F.A. (IIUM Press, 2025)
Hyperventilation syndrome (HVS) is known as exceeding metabolic demands in respiration that usually result in increased heart rate, cardiac output, and respiratory rate. It is also linked to reduced physical and mental health-related quality of life (HRQoL). This study aims to determine the prevalence, symptoms, and factors associated with hyperventilation syndrome and health-related quality of life among undergraduate students. A cross-sectional study was conducted among 178 undergraduate students. The questionnaires distributed consist of three parts which are socio-demographic data, the Nijmegen Symptom Questionnaire (NQ) and the SF-36 questionnaire. There was a significant difference between HVS and HRQoL in physical functioning, role limitations due to physical problems, emotional problems, mental health, vitality, body pain and general health perception (p<0.05). This study's findings highlight the importance of addressing respiratory patterns and their implications on both physical and mental health outcomes among undergraduate students.